Aware of the roots of the text in the arab heritage (Journal of the College of Education for Women, 2019)
Text science presented a set of criteria to make the text essentially a project to createtexts and use. Me and means of cohesion script text scientists, two standard foundries andknitting. Find this means their equivalent in the Arab rhetorical Heritage has been found, itmeans foundries find Accompanying represented (link grammar in the classroom and link),and referrals represented by (Baldmair, Ldefinition, and the name of the signal), anddeletion, and repetition, and presentation delays. As in the standard knitting it has confirmedAlbulagjun Arabs on the semantic consistency between the text components, as reflected inthe moral link in Chapter interfaces, as well as in moral coherence between parts of the text,in the initiation and completion and disposal. Thus other text standards and found its roots inthe inherited rhetoric and grammar. Has addressed that a detailed search